2018
DOI: 10.2134/jeq2017.10.0405
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Sorption Characteristics in Aluminum‐based Water Treatment Residuals Reacted with Dairy Wastewater: 1. Isotherms, XRD, and SEM‐EDS Analysis

Abstract: We examined P sorption characteristics in Al-based water treatment residuals (Al-WTR) generated from slightly alkaline surface water and in an organic residual composite (WW-Al/O-WTR), produced by using the Al-WTR to treat organic-rich and high P concentration dairy wastewater. Solids from both residuals were examined using scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS) and X-ray diffraction (XRD), and exposed to P additions of 0 to 4000 mg L in a sorption experiment. The Al-WTR removed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…This finding is consistent with XRD analyses reported by Zohar et al (2018), which indicated the presence of calcite in the WTR; calcite can act as an adsorbent for P (Sø et al, 2011). Additionally, SEM‐EDS analyses reported by Zohar et al (2018) indicated that P was associated both with Al‐ and Ca‐rich surfaces of WTR particles. The known XANES spectra used to fit the unknown spectra in the WTR samples were from adsorbed P, supporting the contention that adsorption was a dominant retention mechanism.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…This finding is consistent with XRD analyses reported by Zohar et al (2018), which indicated the presence of calcite in the WTR; calcite can act as an adsorbent for P (Sø et al, 2011). Additionally, SEM‐EDS analyses reported by Zohar et al (2018) indicated that P was associated both with Al‐ and Ca‐rich surfaces of WTR particles. The known XANES spectra used to fit the unknown spectra in the WTR samples were from adsorbed P, supporting the contention that adsorption was a dominant retention mechanism.…”
Section: Resultssupporting
confidence: 92%
“…As noted by Zohar et al (2018), and given the high organic matter content of the WTR (Table 1), organic P species are almost certainly present in the WW‐Al/O‐WTR. Therefore, it may seem curious that no explicitly organic P species were detected using P K ‐edge XANES spectroscopy.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…Ajiboye et al (2007) used NMR spectroscopy, chemical extractions, and P K ‐edge XANES analysis to quantify P speciation in organic soil amendments such as manure and biosolids. Similarly, Zohar et al (2018) and Massey et al (2018) combined chemical extractions, scanning electron microscopy with energy dispersive X‐ray spectroscopy (SEM‐EDS), and XANES spectroscopy to quantify speciation in P recovered from wastewater using a mixed Al oxide–calcite sorbent.…”
Section: Discussionmentioning
confidence: 99%